The Role of Regulatory Mechanisms and Environmental Parameters in Staphylococcal Food Poisoning and Resulting Challenges to Risk Assessment - Zeaki, Nikoleta; Johler, Sophia; Skandamis, Panagiotis N.; Schelin, Jenny (Frontiers in Microbiology, 2019)
Staphylococcus aureus is a versatile and widespread foodborne pathogen leading to staphylococcal food poisoning (SFP). SFP is caused by consumption of food containing enterotoxins preformed during S. aureus growth. This review aims to present a comprehensive overview of challenges related to the presence of S. aureus in the food production chain. It focuses on characteristics, expression and regulation of the highly stable staphylococcal enterotoxins and in particular SEA. Together with the robustness of the pathogen under diverse environmental conditions and the range of possible entry routes into the food chain, this poses some of the biggest challenges in the control of SFP. Furthermore, the emergence of new enterotoxins, found to be connected with SFP, brings new questions around their regulatory mechanisms and expression in different food environments. The appearance of increasing amounts of antibiotic resistant strains found in food is also highlighted. Finally, potentials and limitations of implementing existing risk assessment models are discussed. Various quantitative microbial risk assessment (QMRA) approaches have attempted to quantify the growth of the bacterium and production of disease causing levels of toxin under various food chain and domestic food handling scenarios. This requires employment of predictive modelling tools, quantifying the spatiotemporal population dynamics of S. aureus in response to intrinsic and extrinsic food properties. In this context, the armory of predictive modelling employs both kinetic and probabilistic models to estimate the levels that potentiate toxin production, the time needed to reach that levels and overall, the likelihood of toxin production. Following risk assessment, the main challenge to mitigate the risk of S. aureus intoxication is first to prevent growth of the organism and then to hamper the production of enterotoxins, or at least prevent the accumulation of high levels (e.g., >10-20 ng) in food. The necessity for continued studies indeed becomes apparent based on the challenges to understand, control and predict enterotoxin production in relation to the food environment. Different types of food, preservatives, processing and packaging conditions, regulatory networks and different SE-producing S. aureus strains need to be further explored to obtain more complete knowledge about the virulence of this intriguing patho¬gen.